Plasma Technology–Preparing for the Electrified Future - Cha, Min Suk; Snoeckx, Ramses (Frontiers in Mechanical Engineering, 2022)
We refer to the fourth state of matter as plasma, indicating ionized, electrically quasi-neutral gas. Electrical discharge in a gas medium is a normal and easy way of turning the gas into plasma in a moderate pressure condition. The electron temperature, electron density, and gas temperature characterize a quality of plasma. Particularly in the domain in terms of the electron temperature and gas temperature, we have room to design discharges to be a thermal plasma (both electron and gas temperature are in equilibrium) or non-thermal plasma (a couple of orders magnitude higher electron temperature than gas temperature). This indicates that the plasma chemistry, consisting of electron impact reactions and thermochemistry governed by the electron temperature and gas temperature, respectively, can be tailored to a certain extent. In this regard, we believe that plasma technology can be considered as a versatile reaction platform, which can replace and reinforce conventional combustion and catalyst-based ones in an electrified future. This perspective particularly highlights the opportunities for the combustion community in the field of low-temperature plasma technology, elaborating on the leashed potential of plasma chemistry and its similarities with combustion studies.